2018
DOI: 10.1093/nar/gky374
|View full text |Cite
|
Sign up to set email alerts
|

AlloFinder: a strategy for allosteric modulator discovery and allosterome analyses

Abstract: Allostery tweaks innumerable biological processes and plays a fundamental role in human disease and drug discovery. Exploration of allostery has thus been regarded as a crucial requirement for research on biological mechanisms and the development of novel therapeutics. Here, based on our previously developed allosteric data and methods, we present an interactive platform called AlloFinder that identifies potential endogenous or exogenous allosteric modulators and their involvement in human allosterome. AlloFin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 60 publications
0
76
0
Order By: Relevance
“…After SAR 650984 had been identified as an allosteric inhibitor of CD38, it was natural to assume that their binding interface (PDB ID: 4CMH; Figure A) was a potential allosteric site. To explore the potential allosteric site of CD38, an online server—AlloFinder, which uses elegant algorithms such as pocket‐based analysis and support vector machine (SVM) classifier to predict the locations of allosteric sites in proteins—was employed. Two sites, shown as Ι and ΙΙ ( Figure B), were highlighted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After SAR 650984 had been identified as an allosteric inhibitor of CD38, it was natural to assume that their binding interface (PDB ID: 4CMH; Figure A) was a potential allosteric site. To explore the potential allosteric site of CD38, an online server—AlloFinder, which uses elegant algorithms such as pocket‐based analysis and support vector machine (SVM) classifier to predict the locations of allosteric sites in proteins—was employed. Two sites, shown as Ι and ΙΙ ( Figure B), were highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…Allosteric site prediction and hotspot mapping : The potential allosteric site in the C‐terminal structure of huCD38 containing the substrate‐binding and SAR antibody‐binding domains (PDB ID: 4CMH) was identified by use of the online server AlloFinder . The pseudo‐ligands (in magenta in Figure B) in the predicted sites were generated automatically.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicate that the CCD of STAT3 is essential for auto-phosphorylation (Ma et al, 2003; Zhang et al, 2000), and certain proteins could inhibit STAT3 activation by binding to STAT3 CCD domain (Chang et al, 2018; Mattagajasingh et al, 2012). Even K116, a STAT3 allosteric inhibitor, inhibited STAT3 phosphorylation at Tyr705 by binding to the CCD of STAT3 (Huang et al, 2018a). Using molecular docking, we showed that the ASRPS binding region in the CCD domain overlaps with K116 binding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Various theoretical models have been put forward for computational allosteric site prediction tools, such as the structure‐based model in AlloSite, the Normal mode analysis‐based model in PARS and the topology‐based model in STRESS . In addition, very recent advances such as AlloSigMA, which provides a quantitative tool for analyzing the energetics underlying allosteric communication, and AlloFinder, which supplies allosterome analysis and virtual screening and scoring, may also be useful tools for allosteric target identification within PPI systems. As a result, computational prediction of allosteric sites can be exploited as a starting point for the discovery of allosteric PPI modulators.…”
Section: Discussionmentioning
confidence: 99%